ARTEMIS: A Simulator Tool for Heterogeneous Network-on-Chip - Fatemeh Vardi; Ahmad Khadem Zadeh; Midia Reshadi (International Journal of Information and Communication Technology Research, 2017)
Complex homogeneous network-on-chip or heterogeneous network-on-chip increases the need of determining and developing simulation tools for designer to evaluate and comparison network performance. Towards this end, ARTEMIS tool, a matlab based simulator environment is developed. This simulator offers some collections of network configuration regarding to the topology graph, routing algorithm and switching strategy, including allocation scheme for a target application. Consequently, designers can choose the number and depth of virtual channels and the capacity of each link by applying an efficient allocation scheme, which is provided by this tool. Average latency and throughput are evaluation performance metrics that are measured with proposed simulator tool.